Cellular Cholesterol Loss Impairs Synaptic Vesicle Mobility via the CAMK2/Synapsin-1 Signaling Pathway - Atikam Qurban; Mengqi Zhang; Hengbing Zu; Kai Yao (Frontiers in Bioscience-Landmark)
Background: Neuronal cholesterol deficiency may contribute to the synaptopathy observed in Alzheimer’s disease (AD). However, the underlying mechanisms remain poorly understood. Intact synaptic vesicle (SV) mobility is crucial for normal synaptic function, whereas disrupted SV mobility can trigger the synaptopathy associated with AD. In this study, we investigated whether cellular cholesterol deficiency affects SV mobility, with the aim of identifying the mechanism that links cellular cholesterol loss to synaptopathy in AD. Methods: Lentiviruses carrying 3β-hydroxysteroid-Δ24 reductase-complementary DNA (DHCR24-cDNA), DHCR24-short hairpin RNA (DHCR24- shRNA) or empty lentiviral vectors were transfected into SHSY-5Y cells in order to construct DHCR24 knock-down and knock-in models, along with corresponding controls. Filipin III cholesterol staining was employed to visualize membrane and intracellular cholesterol in the different cell models, and fluorescence intensity was assessed using confocal microscopy. Additionally, we performed immunoblotting to quantify the expression of DHCR24, total calmodulin-dependent protein kinase 2 (CAMK-2), p-CAMK2 (T286), caveolin-1, total synapsin-1, phosphorylated synapsin-1 (p-synapsin-1; S605), and synaptophysin in each experimental group. Results: In DHCR24-silenced cells, the loss of cellular cholesterol caused by knock-down of DCHR24 resulted in a significant decrease in the levels of phosphorylated CAMK2 (p-CAMK2) and phosphorylated synapsin-1 (p-synapsin-1) compared to control cells. The reduction in p-CAMK2 and p-synapsin-1 could disrupt SV mobility, thereby reducing replenishment of the readily releasable pool (RRP) from the reserve pool (RP). Furthermore, cells with DHCR24 knock-down showed downregulation of caveolin-1, a crucial lipid raft marker, compared to control cells. Conversely, elevated cellular cholesterol levels caused by knock-in of DHCR24 reversed the effects of cholesterol deficiency, suggesting that CAMK2-mediated synapsin-1 phosphorylation may be regulated in a lipid raft-associated manner. Additionally, we found that cellular cholesterol loss could significantly downregulate the expression of synaptophysin protein, which is vital for SV biogenesis and synaptic plasticity. Conclusion: These results suggest that depletion of cellular cholesterol following knock-down of DHCR24 can decrease synaptophysin protein expression and impair SV mobility by regulating the CAMK2-meditated synapsin-1 phosphorylation pathway, potentially via a lipid raft-associated mechanism. Our study indicates a critical role for cellular cholesterol deficiency in AD-related synaptopathy, thus highlighting the potential for targeting cellular cholesterol metabolism in therapeutic strategies.